Factors Affecting The Exfoliation Corrosion Of Aluminium Alloys - Jackson, N (Cranfield University, 1996)
Aluminium alloys suffer from localised attack termed exfoliation corrosion which is intergranular in nature where the attack proceeds around the elongated grains present in the microstructure. The formation of a more voluminous corrosion product than the original material results in the lifting of grains giving the characteristic of exfoliation corrosion - lamellar attack. This results in surface degredation in the form of pitting, flaking or blistering. The precipitates present within the microstructure and the grain shape can alter how susceptible the material is to exfoliation corrosion. The distribution of precipitates present can be altered by heat treatment which affects the exfoliation corrosion susceptibility. A study on the effects of heat treatment and grain shape on exfoliation corrosion has been completed for two AlCuMg alloys (2014 and 2024) and two aluminium - lithium alloys (8090 and 2091). A MASTMAASIS salt - spray cabinet was used to determine the exfoliation corrosion susceptibility of all the alloys. A four - point bend test was developed to determine the depth of penetration and compared to depths measured metallographically. The results for the 2XXX series alloys suggest that as the grain aspect ratio increases the exfoliation susceptibility increases. Although the aspect ratio did not differ greatly between each alloy, the different phases present in the two alloys seem to contribute more markedly to the susceptibility. Heat treatment in the 2024 alloy suggested that the peak - aged condition gave a higher susceptibility to corrosion than the under - aged and over - aged conditions. Results indicated that the heat treatment has a greater effect on exfoliation corrosion than the grain aspect ratio, showing that the grain boundary microstructure is an important factor in the exfoliation process. The four - point bend test tended to underestimate the depth of attack by virtue of measuring the whole area of the specimen whereas metallographic measurements only took into account the attacked areas. End grain testing suggested that the attack can not only proceed longitudinally but also "short - circuit" down the transverse path of the elongated grains in the 2XXX series alloys. For the aluminium - lithium alloys the over - aged condition showed more resistance to attack than the under - aged and peak - aged conditions but the under - aged was more resistant to attack for the 2091 alloy. Stress corrosion cracking showed trends similar to exfoliation corrosion.